التطوع الاحترافي وعلاقته بتنمية المسؤولية الاجتماعية لدى طالبات كلية التربية بجامعة الزاوية" (Comprehensive Journal of Science, 2026)
Title: Professional Volunteering and its Relationship to Developing Social Responsibility among Students of the Faculty of Education at the University of Zawiya.Objectives: This study aimed to diagnose the reality of professional volunteering among students at the Faculty of Education, University of Zawiya. It sought to measure its impact on enhancing social responsibility dimensions (personal, national, and religious). Furthermore, the study aimed to identify the sociological and organizational obstacles that limit students' involvement in organized voluntary work.Methodology: The study employed a descriptive-analytical approach. A scientifically validated questionnaire was administered to a substantial sample of 2,000 female students. The sample was selected using a simple random sampling method across various academic and pedagogical departments for the academic year 2024-2025.Key Findings:The results revealed a high level of awareness among students regarding the concept of "professional volunteering" and its link to professional duty.The study proved statistically significant differences in social responsibility indicators (commitment, discipline, and effectiveness) in favor of students who participated in voluntary work.Findings indicated that 57.5% of the study sample represents "untapped energy" as they had not engaged in any previous voluntary activities.The most prominent obstacles were time constraints and conflicts between activities and academic schedules (93.3%), followed by the absence of a formal system for accrediting voluntary hours.Recommendations: The study recommended the institutionalization of voluntary work by establishing a specialized administrative unit within the faculty. It also suggested adopting an academic incentive system that includes voluntary hours in the student's academic record, and strengthening partnerships between the university and civil society institutions in the city of Zawiya.
Keywords: Professional Volunteering, Social Responsibility, University of Zawiya, Faculty of Education, Social Work